Case Report: Living donor liver transplantation for the treatment of recurrent pediatric acute liver failure with neuroblastoma amplified sequence gene mutation: a literature review - He, Shengying; Zhao, Yi; jin, Zhu; Xia, Xinrong; Tang, Chengyan; Gong, Yuan; Huang, Lu; Du, Qing; Zhu, Daiwei; Zhou, Wankang; Liu, Yuanmei; Zheng, Zebing (Frontiers in Pediatrics, 2025)
BackgroundBiallelic mutations in the neuroblastoma amplified sequence (NBAS) gene can cause recurrent acute liver failure (RALF) and multi-systemic disease.Case presentationHerein, we report a 3-year-old Chinese boy with RALF due to a novel heterozygote mutation c.3596G>A(p.C1199Y)/c.1028G>A(p.S343N) in the NBAS gene, identified by whole-exome sequencing. The missense mutation c.3596G>A(p.C1199Y) was inherited from his father, and c.1028G>A(p.S343N) was inherited from his mother. He had suffered six acute liver crises triggered by fever. He eventually underwent living donor liver transplantation (LDLT) at 44 months, with his father donating the left lateral lobe liver, and is now healthy with no recurrence of ALF.ConclusionWe describe a novel pathogenic mutation in the NBAS gene of a patient with RALF and report that LDLT is a safe and efficient treatment for RALF caused by the NBAS gene mutation.